Japanese glaciological activities in the Arctic region (report) - Watanabe, Okitsugu (1996)
P(論文) The objectives of the Japanese Arctic Glaciological Expedition were to study the regional characteristics of glacier processes and the climatic and environmental changes for the last few hundred years in the Arctic cryosphere. During 1987-1996,glaciological observation and shallow ice core drilling were carried out at various places such as the Greenland Ice Sheet, Svalbard archipelago and the main land of Norway. departmental bulletin paper